Associations between ethnicity, place of residence, hearing status of family and habilitation of children with hearing impairment - Ester Goldblat; Dori Rivkin; Viacheslav Konstantinov (BMC, 2020)
Abstract Background Hearing parents tend to have a strong preference for their deaf and hard-of-hearing children to acquire adequate speech, as opposed to use of sign language. Research reports the contribution of many variables to speech acquisition by children with hearing loss (HL). Yet, little is known about the association between ethnicity, place of residence, and hearing status of family members and mode of communication of young people with HL. The purpose of the present study was to examine whether mode of communication of young people with HL is associated with ethnicity, place of residence, and hearing status of family members. Method Participants were young adults with sensory-neural severe to profound HL, either congenital or acquired prior to age 3. Only participants without additional disabilities were included. The data on participants were extracted from records of the Ministry of Labor, Social Affairs and Social Services in Israel. The data for each participant in the study included mode of communication, gender, use of assistive device, ethnicity, geographic place of residence, and presence of first-degree relatives with HL. Regarding participants with a cochlear implant (CI), age at implantation was documented as well. Results Chi-square tests revealed significant associations between mode of communication and all of the study variables. In addition, all the study variables made a significant contribution to mode of communication. Regarding ethnicity, most of the ultra-Orthodox participants used oral language, while the majority of Israeli-Arab participants used sign language. Regarding geographical place of residence, lower rates of oral language use were found in the northern and southern districts of Israel. Conclusions The findings of the present study underline the need for better monitoring of Israeli-Arab children with HL and children residing in peripheral areas in Israel and for improving access to habilitation services.